Vivências do cotidiano escolar - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present research was developed as a conclusion of the course of Field Education - Licenciatura, Federal University of Pampa - campus - Dom Pedrito, has as main objective to analyze the effects of the school accompaniment with the family on the school routine. The work is structured as follows, an introduction that brings a history of the researched school, a theoretical reference, which dialogues with authors about the daily school life, which according to Garcia (2003) is a complex space and deserves a multidisciplinary view to account to understand the transformations that take place in it at all times; methodology, which describes action research as the main instrument used and details its steps. Observations were made at school and visits to some families, to know the reality of the same and to understand their understanding of the school, as well as the effects of these accompaniments in the school environment. In the face of research, we can highlight significant changes in the socialization, autonomy and safety of students in school, a fact that demonstrates how valid it was, since it created a link between the social actors involved. Before the analysis we realized that the school should think strategies such as studies and actions that propose a closer relationship between teacher / student, but that such actions are continuous, so that they become meaningful, as it would require a greater space of time to accomplish such but knowing the reality of families and their experiences enriches the exchange between family / school and gives a new meaning to learning and teaching.
Keywords: Educação; Cotidiano escolar; Família; Daily life; Family; Education; CNPQ::CIENCIAS HUMANAS